(untitled) (Circe de clásicos y modernos, 2024)
The construction of Hector as an attractive figure for the audience of the Iliad is a well-studied topic in criticism. Different hypotheses and elements contributing to this effect have been given, but there is clear agreement that the hero, particularly among the Trojans, is one of the most sympathetic to the audience throughout the poem. This paper sets out to study the hero’s speeches and their attunement with the feelings and opinions of the audience, and in general with the emotional tone of the different moments of the poetic performance. We hypothesize that, as Hector’s tragedy unfolds, the relationship between the perception of events manifested in the hero’s words and that of the audience becomes increasingly conflicted, a process that is reversed at the moment when the imminence of his death becomes clear to the character. Thus, we will attempt to demonstrate that the audience’s identification with Hector is not a simple, linear phenomenon, but is manipulated by the poet to generate expectations and anxiety in the audience in order to retain their attention to the epic spectacle.